2023
DOI: 10.3390/atmos14071138
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Microclimate Pattern and Related Spatial Perception of the Urban Stormwater Management Landscape: The Case of Rain Gardens

Abstract: This study examines the microclimate pattern and related spatial perception of urban green stormwater infrastructure (GSI) and the stormwater management landscape, using rain gardens as a case study. It investigates the relationship between different rain garden design factors, such as scale, depth, and planting design, and their effects on microclimate patterns and human spatial perception. Taking an area in Blacksburg, Virginia, as the study site, twelve rain garden design scenarios are generated by combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Rain gardens, when incorporated into the 30% NBS design scenario, prove to be beneficial for improving thermal comfort values when in conjunction with trees and other greening strategies. The microclimatic benefits of the rain gardens found in this study are in accordance with a previous study in Virginia, USA, which analysed the microclimate impacts of 12 types of rain garden design scenarios [28]. This highlighted the role of such a typology of NBS in cities, which can be used not only for sustainable drainage systems and pollutant removal [56] but also for improving the microclimate [27].…”
Section: The Potential Microclimatic Benefits Of Converting Car Park ...supporting
confidence: 88%
See 1 more Smart Citation
“…Rain gardens, when incorporated into the 30% NBS design scenario, prove to be beneficial for improving thermal comfort values when in conjunction with trees and other greening strategies. The microclimatic benefits of the rain gardens found in this study are in accordance with a previous study in Virginia, USA, which analysed the microclimate impacts of 12 types of rain garden design scenarios [28]. This highlighted the role of such a typology of NBS in cities, which can be used not only for sustainable drainage systems and pollutant removal [56] but also for improving the microclimate [27].…”
Section: The Potential Microclimatic Benefits Of Converting Car Park ...supporting
confidence: 88%
“…In the past, concepts such as water-sensitive urban design and sustainable urban drainage systems, incorporating NBS, have been applied and studied by researchers and landscape architects for their ability to address water-related challenges in cities [27]. However, more recent research on bioretention systems or rain gardens has brought to the forefront their role in mitigating the UHI effect and enhancing thermal comfort [27,28]. For example, Kridakorn Na Ayutthaya et al ( 2023) [27] demonstrated that combining bioretention with mature trees can offer additional outdoor thermal comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Especially RG-2A and RG-2B, the TOC contents of RG-2A were > 1.72 times more than RG-2B, while the highest was 1.98 times (3rd sampling). The runoff intercepted in the drained rain gardens migrated to the drainage pipeline, but this also caused runoff pollutants to migrate downward, and more organic pollutants accumulated on the soil surface 37 . However, due to the long interval between the two samplings, the stormwater in the infiltrated rain gardens had enough time to slowly infiltrate, the organic carbon in the facility gradually migrated downward, and the TOC contents level of the surface layer 0–20 cm was low.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, after actual interviews with the subjects, it was learned that in the snow season environment, the low temperatures in the cold regions would largely affect people's walking thoughts, walking speeds, and modes of travel, which would affect the comprehensiveness of the experiment to a certain extent. Although this study explored the influence mechanism of visual perception in snow and non-snow seasons, the experiment did not consider the influence of physical factors such as the temperature [66], humidity [67], and light environment [68]. In future studies, VR experiments will be conducted in combination with a virtual environment warehouse [69,70], the aim will be to restore the same environmental conditions as the actual scenario and to dress the subjects with physiological indicator equipment, using physiological indicators as supplementary indicators for subjective evaluation, which will help to enhance the accuracy of the experiment.…”
Section: Limitations Of Screening Leisure Visual Landscape Environmen...mentioning
confidence: 99%